Initial states of fish of food interest in the south-west region of Mauritius - Bidet, Julien (2023)
The marine environment of Mauritius has suffered from rapid colonization and exploitation of the land since the 16th century. The reefs of Mauritius are today considered at high risk. The decline of coral reef health and fish catch affects fishing yield and could seriously threaten Mauritius' economy. To improve the quality of the marine environment, a project of marine protected area (MPA) implementation has taken place on the south west coast. We used under-water visual census (UVC) as a before-control-impact to investigate the sub population of food interest fishes and the coral coverage of the lagoon and fringing reef of "l'île aux Bénitiers". A relatively low diversity of fishes were observed. A total of 95 species were encountered during the study. We found on average a fishable biomass of 188.4g/100m² in the lagoon, 725.6g/100m² in the back reef, 2042.7g/100m² on the reef and 4950.4g/100m² in the pass. The area presents the characteristics of an over exploited zone with low coral cover; dominance of herbivorous fishes on the reef and the absence of apex predators such as sharks and large groupers or snappers. This paper confirms the necessity of conservation measures within the area. It also provides data that will allow temporal control impact to be performed in the case of MPA implementation.